SOFT SKILLS PROFILE OF STUDENT AS A BIOLOGY TEACHER CANDIDATE THROUGH THE EDUCATION ORIENTED WITH LESSON STUDY IN FKIP PASUNDAN UNIVERSITY - Fitri Aryanti; Cartono Cartono; Ida Yayu Nurul Hizqiyah (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2019)
ABSTRACTThis research is a qualitative descriptive. Data collection done through limited interviews and observation sheets. The results obtained are in the form of soft skills profiles of student as a biology teacher candidate on the implementation of education oriented with lesson study. Score of the accuracy of word selection  60%, score of clarity of the use of words  40%, score of the ability of students to compare various data from several sources 55%, score of analyzing problem relationships 45%, score of identifying the problem 65%, score of limiting the problem 35%, score of contributions to groups 55%, score of member responsibility 45%, score of the ability to manage an organization is the quality of information sources 50%, score of the quality of information management 50% and score of the honesty 70%. The  expansion   implementation  program  in   schools planned to be carried out in further research Keywords:soft skills profile, student as a biology teacher candidate, lesson study ABSTRAKPenelitian ini adalah deskriptif kualitatif. Pengumpulan data dilakukan melalui wawancara terbatas dan lembar observasi. Hasil yang diperoleh berupa profil soft skill siswa sebagai calon guru biologi pada pelaksanaan pendidikan yang berorientasi pada lesson study. Skor ketepatan pemilihan kata 60%, skor kejelasan penggunaan kata 40%, skor kemampuan siswa untuk membandingkan berbagai data dari beberapa sumber 55%, skor analisis masalah hubungan 45%, skor identifikasi masalah 65%, skor membatasi masalah 35%, skor kontribusi kepada kelompok 55%, skor tanggung jawab anggota 45%, skor kemampuan mengelola organisasi adalah kualitas sumber informasi 50%, skor kualitas manajemen informasi 50% dan skor kejujuran 70%. Program implementasi perluasan di sekolah direncanakan akan dilakukan dalam penelitian lebih lanjut. Kata kunci:profil soft skill, mahasiswa sebagai calon guru biologi, lesson study